Pembinaan dan Pengawasan dalam Penyelenggaraan Perparkiran oleh Dinas Perhubungan Kota Padang - Putri, Vinny Meiska; Mubarak, Adil (Lembaga Yasin AlSys, 2025)
The implementation of guidance and supervision in the management of parking services in Padang City has not yet operated optimally, as evidenced by the ongoing issues within the current parking system. This study aims to analyze the forms and effectiveness of the guidance and oversight conducted by the Padang City Department of Transportation in parking management. A qualitative method with a descriptive approach was employed. Data were collected through interviews, observation, and documentation. The findings reveal that the implementation of guidance remains largely formalistic and has yet to address educational aspects or significantly enhance the overall professionalism of parking attendants. Meanwhile, supervision is limited to specific times and locations, failing to reflect comprehensive and continuous monitoring. The study concludes that to establish an orderly, transparent parking system that contributes to Local Own-Source Revenue (PAD), it is essential to strengthen human resource capacity, improve supervision mechanisms, and foster closer collaboration between the government and the community. Keywords: Guidance; Supervision; Parking Management; Department of Transportation; Padang City